Hydrogen-Borrowing Alkylation of 1,2-Amino Alcohols in the Synthesis of Enantioenriched γ-Aminobutyric Acids - Hall, CJJ; Goundry, W; Donohoe, T (Wiley, 2021)
For the first time we have been able to employ enantiopure 1,2‐amino alcohols derived from abundant amino acids in C‐C bond forming hydrogen borrowing alkylation reactions. These reactions are facilitated by the use of the aryl ketone Ph*COMe. Racemisation of the amine stereocentre during alkylation can be prevented by the use of sub‐stoichiometric base and protection of the nitrogen with a sterically hindered triphenylmethane (trityl) or benzyl group. The Ph* and trityl groups are readily cleaved in one pot to give γ‐aminobutyric acid (GABA) products as their HCl salts without further purification. Both steps may be performed in sequence without isolation of the hydrogen borrowing intermediate, removing the need for column chromatography.